Nabbed! 1925 : the journal of G. Codd Fitzmorgan - Doyle, Bill H., 1968- (New York : Little, Brown, 2006)
In 1925, fourteen-year-old amateur detective G. Codd Fitzmorgan finds himself at a lavish party in a storm-battered island mansion, embroiled in a mystery involving a seance, a missing aviator, and the sale of liquor banned under Prohibition.
Keywords: Prohibition -- Fiction; Aeronautics -- History -- Fiction; Mystery and detective stories; North Carolina -- History -- 20th century -- Fiction